Prenatal diagnosis and follow-up of fetal cardiac tumors: case series and review of the literature - Roa Carrasco, Tania (2023)
Background: Cardiac tumors are frequent in the fetal and infant stages, withrhabdomyoma being the most prevalent in fetal life. Its diagnosis has increased dueto ultrasound screening. Objective: To report the first Peruvian series of cases withprenatal diagnosis of fetal cardiac tumors in a maternal perinatal institute. Methods:Descriptive study of case series. The database of all fetuses with prenatal diagnosisof cardiac tumors from January 2009 to January 2021 at the Instituto NacionalMaterno Perinatal (INMP), Lima, Peru, was reviewed. These patients were followedup by telephone and in two cases echocardiographic control was performed. Results:We found 6 cases of patients diagnosed with cardiac tumors in the last 12 years inthe INMP, with reduction in size in the follow-up of all cases and association withtuberous sclerosis in half of them. Conclusions: Cardiac rhabdomyomas representthe most frequent tumors in fetal life. Most of them have in common the partialremission of the tumor. However, the clinical evolution depends on the location ofthe tumor, size, and its association or not with tuberous sclerosis. For this reason,close follow-up is recommended, especially of the central nervous system.